The Role of the Regional Library and Archives Office in Improving the "Love Reading" Program Through Mobile Libraries for Elementary School Students in the South Tapanuli Regency - Hamonangan Harahap (International Journal of Integrated Science and Technology, 2024)
This research aims to determine the role of the Regional Library and Archives Office in enhancing the love of reading program through mobile libraries for elementary school students in South Tapanuli Regency, as well as the obstacles and challenges faced by the Regional Library and Archives Office in improving the love of reading program through mobile libraries for elementary school students in South Tapanuli Regency. This research uses a descriptive method with a qualitative approach, and data is collected through direct observation and interviews with librarians. Sample selection is done using purposive sampling technique. The research results indicate that the stages of mobile library services in the implementation of the literacy movement activities are as follows: 1) Preparation stage, consisting of two steps, which are providing literacy materials and facilitator training. 2) Implementation stage, consisting of one step, which is through learning activities. 3) Evaluation/follow-up stage, consisting of one step, which involves conducting a national literacy Olympiad. Efforts to overcome the challenges faced by librarians in implementing mobile libraries include: 1) Human Resources, in this case, the staff. Efforts are made through collaboration with the existing Health and Safety Committees (K3S). Additionally, for mentors, efforts are made by working professionally. 2) Budget, efforts to address the lack of books involve cross-referencing books and applying for procurement or deposits. Efforts for teaching aids involve using the library staff's own resources. Addressing access equipment challenges is done by using any means available to transport books to locations that are not accessible by four-wheeled vehicles.